Fitness attenuates long-term cardiovascular outcomes in women with ischemic heart disease and metabolic syndrome - Odayme Quesada; Marie Lauzon; Rae Buttle; Janet Wei; Nissi Suppogu; Galen Cook-Wiens; Steven E. Reis; Leslee J. Shaw; George Sopko; Eileen Handberg; Carl J. Pepine; C. Noel Bairey Merz (American Journal of Preventive Cardiology, 2023)
Background: The prevalence of metabolic syndrome continues to increase steadily while fitness remains relatively low. The contribution of fitness on longer-term cardiovascular outcomes and mortality in individuals with cardiovascular disease and metabolic syndrome remains unknown. Design: Women's Ischemia Syndrome Evaluation (WISE) prospective cohort (enrolled 1996–2001) of women undergoing invasive coronary angiography with signs/symptoms of ischemic heart disease. Methods: Investigated the association of fitness, defined as >7METs measured by self-reported Duke Activity Status Index (DASI), and both metabolic syndrome (ATPIII criteria) and dysmetabolism (ATPIII criteria and/or treated diabetes) with long-term cardiovascular outcomes and all-cause mortality risk. Results: Among the 492 women followed for a median of 8.6 years (range 0–11 years), 19.5% were fit-metabolically healthy (reference), 14.4% fit-metabolic syndrome, 29.9% unfit-metabolically healthy, and 36.2% unfit-metabolic syndrome. Compared to reference, MACE risk was 1.52-fold higher in fit-metabolic syndrome women (HR 1.52, 95% CI 1.03–2.26) and 2.42-fold higher in unfit-metabolic syndrome women (HR 2.42, 95% CI 1.30–4.48). Compared to reference, mortality risk was 1.96-fold higher in fit-dysmetabolism (HR 1.96, 95% CI 1.29–3.00) and 3-fold higher in unfit-dysmetabolism women (HR 3.0, 95% CI 1.66–5.43). Conclusions: In a high risk cohort of women with signs/symptoms of ischemic heart disease, unfit-metabolically healthy and fit-metabolically unhealthy women were at higher risk of long-term MACE and mortality compared to fit-metabolically healthy women; and women who were unfit and metabolically unhealthy were at the highest risk. Our study demonstrates that metabolic health and fitness play an important role in long term outcomes that warrants further investigation. Registration: https://www.clinicaltrials.gov/ct2/show/NCT00000554 (NCT00000554)